On Current Conversion between Particle Rapidity and Pseudorapidity Distributions in High Energy Collisions - Fu-Hu Liu; Ya-Hui Chen; Ya-Qin Gao; Er-Qin Wang (Advances in High Energy Physics)
In high energy collisions, one usually needs to give a conversion between the particle rapidity and pseudorapidity distributions. Currently, two equivalent conversion formulas are used in experimental and theoretical analyses. An investigation in the present work shows that the two conversions are incomplete. Then, we give a revision on the current conversion between the particle rapidity and pseudorapidity distributions.